PENGARUH GREEN PRODUCT, GREEN BRAND, DAN GREEN ADVERTISING TERHADAP KEPUTUSAN PEMBELIAN - Wiwoho, Gunarso (P4M STIE Putra Bangsa, 2015)
This study aims to determine the effect of Green Product, Green Brand, and Green Advertising on Tupperware Purchasing Decisions in Kebumen. The purpose of this study is to analyze and explain the effect between the independent variable and the dependent variable. The sample in this study are consumers who know, buy, or use Tupperware in the amount of 100 people. Data collection techniques using purposive sampling technique. Validity test shows that all variables in this study are valid. The data is processed using the SPSS 22 for Windows program. Based on the results of the study indicate that the Green Product variable has a significant effect on purchasing decisions. Green Brand has a significant influence on purchasing decisions. Green Advertising has a significant effect on purchasing decisions.